Programming Digital Transformation for Revitalizing Rural Economies in Puhsarang Village - Memarista, Gesti; Agung, Deatri Arumsari; Yuniarto, Antonius; Heng, Boon Kang; Sulla, Nyle Casey M. (UI Scholars Hub, 2025)
The disruptive situations, such as the COVID-19 pandemic, have intensified economic challenges in rural areas, underscoring the urgency of building rural economic resilience. This study explores a model for revitalizing the local economy in Puhsarang Village in East Java, Indonesia. The project was developed as a community service collaboration among universities in Indonesia, Malaysia, and the Philippines, programming a digital transformation for a tourism-based context. Seventeen micro, small, and medium enterprises (MSMEs) participated in the community service project, selected through purposive sampling in collaboration with the local church. Entrepreneurs, ranging from religious souvenir shops to food vendors, benefited from a tailored program in product development and digital marketing. The impact of the service-learning was studied by employing a mixed-methods approach. The data was collected through qualitative interviews and questionnaires and analyzed quantitatively as a post-program evaluation. Key findings highlight the potential of semi-outdoor diners, woodcraft workshops, and religious tourism products to expand market reach via online platforms. The collaboration community program engaged seven lecturers and 27 students to apply academic knowledge and intercultural skills in real-world settings, with above-average evaluation scores reflecting its impact. Results show increased sales and improved business capacity among participants, as perceived benefits and experiential outcomes of the program. This initiative demonstrates how cross-cultural collaboration in community service, when aligned with digital transformation strategies, can foster sustainable and inclusive growth, offering practical insights for strengthening rural economies in line with the SDGs.